Intra-individual comparison of PET/CT with different body weight-adapted FDG dosage regimens. (29th January 2015) - Geismar, Jan H; Stolzmann, Paul; Sah, Bert-Ram; Burger, Irene A; Seifert, Burkhardt; Delso, Gaspar; von Schulthess, Gustav K; Veit-Haibach, Patrick; Husmann, Lars
Background: 18F-2-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET)/ computed tomography (CT) imaging demands guidelines to safeguard sufficient image quality at low radiation exposure. Various FDG dose regimes have been investigated; however, body weight-adapted dose regimens and related image quality (IQ) have not yet been compared in the same patient. Purpose: To investigate the relationship between FDG dosage and image quality in PET/CT in the same patient and determine prerequisites for low dosage scanning. Material and Methods: This study included 61 patients undergoing a clinically indicated PET/CT imaging study and follow-up with a normal (NDS, 5 MBq/kg body weight [BW]) and low dosage scanning protocol (LDS, 4 MBq/kg BW), respectively, using a Discovery VCT64 scanner. Two blinded and independent readers randomly assessed IQ of PET using a 5-point Likert scale and signal-to-noise ratio (SNR) of the liver. Results: Body mass index (BMI) was significantly lower at LDS ( P  = 0.021) and represented a significant predictor of SNR at both NDS ( P  < 0.001) and LDS ( P  = 0.005). NDS with a mean administered activity of 340 MBq resulted in significantly higher IQ ( P  < 0.001) and SNR as compared with LDS with a mean of 264 MBq (F-value = 23.5, P  < 0.001, mixed model ANOVA adjusted for covariate BMI). Non-diagnostic IQ at LDS was associated with a BMI > 22 kg/m 2 . Conclusion: FDG dosage significantly predicts IQ and SNR in PET/CT imaging as demonstrated in the same patient with optimal IQ achieved at 5 MBq/kg BM. PET/CT imaging at 4 MBq/kg BW may only be recommended in patients with a BMI ≤ 22 kg/m 2 to maintain diagnostic IQ.